Geometric contributions to chopper wheel optical attenuation uncertainty. (28th June 2017) - Spidell, M; Hadler, J; Stephens, M; Williams, P; Lehman, J
Abstract: Calibrated optical choppers are used in high-power laser calibration services at the National Institute of Standards and Technology for beam power reduction due to their advantages in performance and safety over wedges and semi-transparent materials. While the design, operation, and calibration of such choppers is generally straightforward, fabrication tolerances and edge geometry must be taken into account for low transmission (<5%) choppers now required to accommodate the increased powers (upwards of 10 kW) available for the calibration service. The slit edge is presented to the beam at non-zero angles of incidence and for edge thicknesses on order of 10% of the slit width, the relative error from design transmission can exceed 2% (depending on beam diameter and angle of incidence). Both slit edge presentation at non-zero angles of incidence and displacement of the slit edges due to minor variation in fabrication or coating yield significant changes in transmission with radial displacement of the beam over the chopper face. While diffraction effects play a smaller role under typical setup conditions, they become an appreciable factor for detectors having small entrance apertures or located far from the chopper wheel. Here we demonstrate a close agreement between the calculated and measured transmission ratio for two optical choppers when considering these three effects.